PENGARUH KUALITAS PELAYANAN,PROMOSI PENJUALAN DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN INDOMARET CABANG SADAI BENGKONG - Ho, Kevin; Saputra, Asron (LPPM Universitas Putera Batam, 2022)
The purpose of this study is to find the effect of service quality, sales promotion and brand image on customer loyalty at the Sadai Bengkong branch Indomaret. The sampling technique used was purposive sampling method where the selected sample were customers who had made transactions at Indomaret and the age limit was 17 years and over with a total of 356 samples.The study uses a Likert scale, the variables to be measured are translated into indicators of data source variables obtained through primary data and secondary data. the data is processed with the windows application SPSS version 25. The data were processed using multiple linear regression statistical tests. The results showed that the service quality variable with a value of Sig 0.002 <0.05, the sales promotion variable with a value of 0.000 <0.05 and the brand image variable 0.000 <0.05 had a significant influence on customer loyalty at Indomaret Sadai Bengkong branch. The variables of Service Quality, Sales Promotion and Brand Image with a sig value of 0.000 <0.05 have a simultaneous effect on customer loyalty